Indonesian Geriatrics Society Consensus on COVID-19 Management in Older Adults - IGP Suka Aryana; Siti Setiati; Roza Mulyana; Noto Dwimartutie; Aulia Rizka; Bayu Basuki Wijaya; Nur Riviati; Rensa Rensa; Dina Aprilia Ariestine; Bambang Joni Karjono; Eko Aribowo; Hildebrand Hanoch Victor Watupongoh; et al. (Acta Medica Indonesiana)
More than 80% of death cases and 95% of severe COVID-19 occur in patients aged over 60 years. Atypical clinical manifestations with high morbidity and mortality further emphasize the importance of COVID-19 management in older adults. Some older patients may appear asymptomatic while other may present with acute respiratory distress syndrome and multi organ failure. Fever, higher respiratory rate and crackles may present. The most common chest x-ray finding is ground glass opacity. Other imaging modalities that are often used are pulmonary computed tomography scan and lung ultrasonography. COVID-19 management in older adults should be comprehensive, starting from oxygen, fluid, nutritional, physical rehabilitation, pharmacology and psychosocial therapy. In this consensus, we also discuss about management of older adults with special condition such as diabetes mellitus, kidney disease, malignancy, frailty, delirium, immobilization and dementia. In post COVID-19 phase, we believe that physical rehabilitation is important as it is done to improve fitness.